Description Of Knowledge Level Of Antibiotic Drug Use In Tanjungmojo Village, Kangkung District, Kendal Regency - Haini Santi; Elvira Rosa; Gigih Anggi Ardiansyah (International Journal of Health Engineering and Technology, 2024)
The level of public knowledge about the use of antibiotic drug classes is still low and causes a high level of irrational use. This study is a descriptive study. Data collection was carried out by survey, namely meeting respondents directly by giving questionnaires. The results showed that the level of knowledge on the use of antibiotic class drugs in tanjungmojo village, kangkung kendal district was still lacking. This can be seen from the results of the questionnaire. The average of the last education taken by respondents in tanjungmojo village , kendal regency was at the sma/smk level. The average occupation of respondents in tanjungmojo village, kangkung district, kendal regency is labor. The level of knowledge in tanjungmojo village, kangkung district, kendal regency, is categorized as moderate , this can be seen from the results of research between the highest level of knowledge and the lowest level of knowledge.